A Calorimetric Study of the Glass Transition Behaviors in Axes of Bean Seeds with Relevance to Storage Stability. - Leprince, O. (1995)
Although the presence of intracellular aqueous glasses has been established in seeds, their physiological role in storage stability is still conjectural. Therefore, we examined, using differential scanning calorimetry, the thermal behavior of glass transitions in axes of bean (Phaseolus vulgaris L.) with water contents (WC) between 0 and 1 g H2O/g dry weight (g/g) and temperatures between -120 and +120[deg]C. Three types of thermal behaviors associated with the glass transition were observed. The appearance, the glass -> liquid transition temperature, and the amount of energy released during these transitions were dependent on the tissue WC. No glass transitions were observed at WC lower than 0.03 and higher than 0.45 g/g. A brief exposure to 100[deg]C altered the glass properties of tissues with WC between 0.03 and 0.08 g/g but did not affect the thermal behavior of glasses with higher WC, demonstrating that thermal history is important to the intracellular glass behavior at lower WC. Correspondence of data from bean to models predicting the effects of glass components on the glass -> liquid transition temperature suggests that the intracellular glasses are composed of a highly complex sugar matrix, in which sugar and water molecules interact together and influence the glass properties. Our data provide evidence that additional glass properties must be characterized to understand the implications of a glassy state in storage stability of seeds.